Penerimaan Generasi Z Terhadap Budaya Patriarki dalam Film Yuni - Ayu, Cempaka Laras; Indriastuti, Yudiana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Films can influence their acceptance and behavior. Yuni’s film raises the issue of social pressure on women, reflecting patriarchal culture in Indonesia. Generation Z is more sensitive to issues of diversity, sustainability, and authenticity, thus being attracted to socially relevant messages. This study aims to analyze Generation Z’s acceptance of patriarchal culture in Yuni’s film using Stuart Hall’s reception analysis theory. The method used is descriptive qualitative with data collection through in-depth interviews with eight informants. Based on the research results, the eight informants showed diverse understandings. There were five informants in the dominant hegemonic position, three informants in the negotiation position, and no informants in the opposition position. The informants’ acceptance positions depend on the diversity of backgrounds, knowledge, and experiences. Generation Z said the form of patriarchal culture in Yuni’s film is relevant to reality and hope that films like this will be made again in the future.